THE EFFECT OF THE FIRST AID SOCIALIZATION IN ACCIDENTS TO INCREASING YOUTH SKILLS IN HANDLING EMERGENCIES IN DAILY LIVING - Priyo Mukti Pribadi Winoto; Difran Nobel Bistara (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2019)
Background: First aid is an initial action that must be immediately given to victims who experience emergency problems due to an accident or emergency incident or by sudden illness before the arrival of an ambulance, doctor or other related officer. Emergency First Aid Issues are often still considered by most people as the sole responsibility of health workers. Even though the reality in the field of participation or community involvement can be very influential, ranging from reducing pain, alleviating suffering, to saving one's life.Objectives: The purpose of this study was to determine the first aid socialization in accidents to increasing youth skills in handling emergencies in daily living in the Jedong Cangkring Village, Prambon Sub-District, Sidoarjo District, East Java Province, Indonesia.Method: This research is a quantitative study with a quasy experiment design with a pretest-post-test control group design approach. The sample in this study was taken with a simple random sampling technique. The method of data collection uses primary data, by providing socialization in the form of counseling and demonstration, then looking at youth skills by using the checklist. Data analysis using Wilcoxon Signed Rank Test and Mann Withney U Test with a significance level of 0.05.Results: The results showed 45% of respondents aged 19-21 years, 55% of respondents had never received information about P3K, 55% of respondents had a school status with a secondary education level, 60% of respondents had sufficient knowledge about first aid. Statistical analysis with the Wilcoxon Signed Rank Test obtained ρ = 0.003<α = 0.05, which means there is an effect of socialization on skills. Mann Withney U Test results obtained ρ = 0.023<α = 0.05, which means there are different skills between the intervention group and the control group.Conclusion: The influence of the first aid socialization in accidents to increasing youth skills in handling emergencies in daily living. Nurses are expected to be able to improve community understanding and skills regarding emergency management in the community. Keyword: Youth skill, first aid socialization, emergency accidents.